Simulation approach for common female cancers: a brief review - Shen, Ying; Li, Chan; Tang, Mao-Yan; Huang, Zhen-Yu (Frontiers in Oncology, 2025)
Simulation approach involves the use of computers and mathematical models to simulate real systems for experimentation or tests that evaluate the behavior and performance of a system or predict the results of various hypothetical scenarios. Due to its rapid development in the context of cancer, we introduce commonly used cancer simulation approach, and review the application of these approach in common cancers of women, such as breast, cervical, ovarian and endometrial cancers, to provide new ideas and directions for cancer study as well as clinical treatment.